Within-person coupling of estradiol, testosterone, and cortisol in women athletes - Edwards, David A. (PeerJ, 2020)
PURPOSE: In variety of settings cortisol and testosterone are positively “coupled.” That is, within-person fluctuations of cortisol and testosterone levels occur in parallel—increases and decreases in one hormone are associated with corresponding increases and decreases in the other. The present report explored hormone coupling in women athletes in two studies selected because they included measurements of salivary levels of cortisol, testosterone, and estradiol—a hormone that has been only infrequently studied in the context of competitive athletics. METHODS: Consenting members of Emory University’s varsity volleyball and soccer teams gave saliva samples on multiple occasions in the run-up to and over the course of two different intercollegiate contests. RESULTS: Volleyball and soccer players showed remarkably similar hormone-specific patterns of increase in relationship to the different stages of competition—before warm-up, after warm-up, and after competition. For both the volleyball and soccer team, Hierarchical Linear Model (HLM) analyses showed estradiol as being significantly coupled with testosterone which was also coupled with cortisol. CONCLUSIONS: This is, apparently, the first report of significant within-person coupling between estradiol and testosterone in the context of competitive athletic stress. These two hormones may be coupled in a wide variety of circumstances not limited to ones involving sport competition, and results reported here should encourage exploration of the extent to which coordinated fluctuations in estradiol, testosterone, and cortisol levels are present in other, more neutral settings and the ways in which the coordination of these fluctuating hormone levels may benefit human performance.